2019
DOI: 10.1002/capr.12272
|View full text |Cite
|
Sign up to set email alerts
|

A thematic analysis of practitioners' understanding of domestic abuse in terms of post‐traumatic stress disorder (PTSD) and complex‐PTSD (C‐PTSD)

Abstract: There is a growing body of evidence suggesting that domestic abuse (DA) should be conceptualised within the complex post‐traumatic stress disorder (C‐PTSD) model. Recently, in the draft of the International Classification of Diseases, Eleventh Revision, produced by the World Health Organization (WHO), C‐PTSD was included as a separate criterion in which DA is incorporated (ICD‐11, WHO, 2018). In this study, a thematic analysis was used to explore to what extent practitioners working with DA survivors are famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Based on these findings, an important future research priority will be to assess the prevalence of CPTSD following exposure to community violence in Brazil as well as in other countries with high levels of community violence in the region. Additionally, as the diagnosis of CPTSD becomes more recognised, an additional future research questions concerns whether and how it will be used in clinical practice by health professionals working in settings characterised by elevated rates of complex trauma [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, an important future research priority will be to assess the prevalence of CPTSD following exposure to community violence in Brazil as well as in other countries with high levels of community violence in the region. Additionally, as the diagnosis of CPTSD becomes more recognised, an additional future research questions concerns whether and how it will be used in clinical practice by health professionals working in settings characterised by elevated rates of complex trauma [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current reality of war in Eastern Europe testifies to immeasurable misery, so it is intuitively understandable that this enormous stressor influences everything, including individual pain perception. Similarly, the assessed relationship problems might also encompass domestic abuse in the sense of controlling, coercive, threatening behavior, violence, or abuse in a relationship, likely causing tremendous distress and suffering [8,38]. In support of this reasoning, both war experiences and relationship problems in the sense of domestic abuse and violence have been shown to lead to a severe dysregulation of the HPA axis, being also evident in PTSD and being associated with higher pain sensitivity [15,39].…”
Section: Discussionmentioning
confidence: 97%
“…The World Health Organization also officially recognizes the diagnosis of complex posttraumatic stress disorder (C-PTSD) in the International Disease Classification ( ICD-11 ), published in 2022. Currently, several studies have shown that the traumatic reactions referred to by PTSD and C-PTSD are different (Barbieri et al, 2019; Frewen et al, 2019; Kozlowska, 2020; Litvin et al, 2017; S. Murphy et al, 2016; Rocha et al, 2020).…”
Section: The Impact Of Complex Trauma On Male Depressionmentioning
confidence: 99%